Pita Maha ‘Koalisi’ Estetik Seni Lukis Klasik Bali dengan Seni Rupa Modern - Arya Sucitra (Ars: Jurnal Seni Rupa dan Desain, 2012)
Te current Balinese culture is the resultof the acculturation of the local culture andthose that come from outside the island. Teacculturation process brings about a variety of stylesand ornamental hybrids that can be identifedapparently in architecture, dance, clothing, and ofcourse visual art.Tis paper attempts to fnd out the spirit ofthe transformation by reading the history of art.Te aesthetics of Balinese visual art is based onthe combination concept of the classical Balinesepainting and the Western modern art movements.Te study is done by studying the achievementsaccomplished by the Pita Maha. Signifcantchanges have taken place in the frameworkof Balinese art. From the technical point ofview, the introduction of paper, plywood andcanvas as painting media provides new stylisticopportunities. Meanwhile from the thematicperspective, secularization of representation occurs;it no longer performs the religious function butholds an economic value. Strong inﬂuence ofmodern science is seen at the organization of spacein the composition, perspective and anatomicalconsideration. Wayang (shadow puppet) fgures arenot dominated by formal form anymore.